THEORETICAL ASPECTS OF DETERMINING THE ESSENCE OF ETHICAL COMPETENCE OF A FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2022)
In clause theoretical aspects of understanding the essence of ethical competence of the future teacher are investigated. The author does attempt to define the basic substantial characteristics of the researched concept.
Keywords: ethical competence; pedagogical ethics; system; development; the future teacher